TUGAS PERKEMBANGAN REMAJA TAHAP AWAL DAN AKHIR - Isma Pebriyanti Harahap; Syaidah Gustina; Rahmah Yasrah Dalimunthe; Sri Wahyuni (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The purpose of this study is to find out the theory of student development. This type of research is library research. This research makes Library materials as its main data source. One of the characteristics of Indonesian society is belief in God Almighty. Religion for humans, especially the Indonesian nation, is an important essential element for life Similarly, in adolescents, it is based on a survey conducted by Laura and Hugh on the tendency of spirituality and religiosity of adolescents in 16 countries. From the survey results, Indonesia has a higher value of spirituality and religiosity than other countries. If you look at the results of the survey, religion should be able to provide life guidelines for adolescents. Religion should be able to foster the mentality of adolescents so that they can live orderly lives and provide a sense of security, peace, and peace in society. Juvenile delinquency itself has a broad meaning, not just a form of unlawful acts committed by children and adolescents but can be even broader. Juvenile delinquency behavior can be in the form of actions that deviate from norms, regulations, and religion in the family, school environment, and also the surrounding community.